2022
DOI: 10.3390/nu14163368
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Vaccine-Induced Human Milk SARS-CoV-2 IgG, IgA and SIgA Immunoglobulins across Simulated Human Infant Gastrointestinal Digestion

Abstract: Breastfeeding can be a vital way of acquiring passive immunity via the transfer of antibodies from the mother to the breastfeeding infant. Recent evidence points to the fact that human milk contains immunoglobulins (Ig) against the SARS-CoV-2 virus, either after natural infection or vaccination, but whether these antibodies can resist enzymatic degradation during digestion in the infant gastrointestinal (GI) tract or indeed protect the consumers remains inconclusive. Herein, we evaluated the levels of IgG, IgA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A study evaluating IgG, IgA and secretory IgA antibody levels of SARS‐CoV‐2 in nursing mothers who received at least two doses of either mRNA‐based or adenovirus‐based vaccine showed that IgG of SARS‐CoV‐2 was degraded in the digestive tract of infants. The study also showed that IgG of SARS‐CoV‐2 was easily degraded in the gastrointestinal tract of infants 32 . Similarly, a study of breast milk samples from nursing mothers who received mRNA vaccination against SARS‐CoV‐2 reported that gastrointestinal digestion of infants significantly decreased the levels of anti‐SARS‐CoV‐2 IgA and IgG 33 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A study evaluating IgG, IgA and secretory IgA antibody levels of SARS‐CoV‐2 in nursing mothers who received at least two doses of either mRNA‐based or adenovirus‐based vaccine showed that IgG of SARS‐CoV‐2 was degraded in the digestive tract of infants. The study also showed that IgG of SARS‐CoV‐2 was easily degraded in the gastrointestinal tract of infants 32 . Similarly, a study of breast milk samples from nursing mothers who received mRNA vaccination against SARS‐CoV‐2 reported that gastrointestinal digestion of infants significantly decreased the levels of anti‐SARS‐CoV‐2 IgA and IgG 33 .…”
Section: Discussionmentioning
confidence: 82%
“…The study also showed that IgG of SARS-CoV-2 was easily degraded in the gastrointestinal tract of infants. 32 Similarly, a study of breast milk samples from nursing mothers who received mRNA vaccination against SARS-CoV-2 reported that gastrointestinal digestion of infants significantly decreased the levels of anti-SARS-CoV-2 IgA and IgG. 33 Additionally, a study examining the breakdown of antiphlogistic syncytial virus sIgA/IgA and IgG in human milk from four donors reported a reduction to 33% in the intestinal stage of simulated digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Breast-milk-derived SARS-CoV-2-specific antibodies have been detected in significant amounts in the breastfeeding infants' saliva and stool, 64,65,68 and studies performed in vitro support the capability of breast-milk-derived anti-SARS-CoV-2 IgG and secretory IgA to resist degradation in the infant gut. 69,70 Importantly, however, anti-SARS-CoV-2 antibodies have not been detected in the blood of infants whose mothers were vaccinated during lactation only, 29,68 suggesting that maternally derived antibodies from breast milk likely do not cross the gut mucosal barrier in detectable quantities. This stands in contrast to antibodies that are transplacentally transferred from mothers vaccinated during pregnancy, which are detectable in the infant's circulation for up to 6 months in the majority of cases.…”
Section: Benefits Of Maternal Covid-19 Mrna Vaccination To the Breast...mentioning
confidence: 99%
“…In this respect, secretory (s)IgA increased at the second dose and 3 weeks after the second dose and decreased at 6 months thereafter, while sIgG levels increased during the second dose and 3 weeks afterwards with maximum levels (peak) at 6 months after the first dose. Additionally, Pieri et al 26 have shown that after maternal vaccination, across simulated human infant gastrointestinal digestion, breastmilk IgA immunoglobulins are resistant to degradation in both the gastric and intestinal phase of the infant digestion, that IgG immunoglobulins are prone to degradation in both phases and that sIgA ones are highly resistant to the gastric phase, although they decline somewhat during the intestinal phase.…”
Section: Are Maternal Covid‐19 Vaccinations During Lactation Safe And...mentioning
confidence: 99%